The Academic Advisor: A New Profile for Guidance and Tutorial at University - Amor Almedina, María Isabel (2016)
Currently, we are in a very important moment to strengthen guidance and tutoring at University level. In this context, the integral formation of students is essential to attend their personal, academic and professional development. Spanish universities have reflected this by establishing lines of action related to our student's guidance. In this work we show the development of actions and experiences, that attempt to respond to these approaches, presenting the results of a study in the Educational Sciences School of the Córdoba University, which purpose was to identify the possible failures and strengths arising during the academic advising program, a model of intervention for guidance at this University. This research was included in an exploratory, descriptive and correlational investigation. 49 students and 14 teachers were chosen from an intentional sampling to take part. The results show that guidance is considered necessary by students for their comprehensive development and university career. Teachers also consider this discipline necessary and as a complement for their teaching labor.